2008
DOI: 10.1042/bj20081798
|View full text |Cite
|
Sign up to set email alerts
|

A novel role of the C-terminus of b0,+AT in the ER–Golgi trafficking of the rBAT–b0,+AT heterodimeric amino acid transporter

Abstract: The heterodimeric complex composed of rBAT (related to b(0,+) amino acid transporter), a single-membrane-spanning glycosylated heavy chain, and b(0,+)AT, a putative 12-membrane-spanning non-glycosylated light chain, is an amino acid transporter that mediates the activity of system b(0,+), a major apical transport system for cystine and dibasic amino acids in renal proximal tubule and small intestine. The C-terminus of b(0,+)AT has been proposed to play an important role in the functional expression of the hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…One of the known functions of heavy chains of HATs is to localize the light chains to the plasma membrane (19,(23)(24)(25)(26). To examine the role of rBAT in the localization of AGT1, AGT1 was expressed with rBAT in HEK293 cells.…”
Section: Resultsmentioning
confidence: 99%
“…One of the known functions of heavy chains of HATs is to localize the light chains to the plasma membrane (19,(23)(24)(25)(26). To examine the role of rBAT in the localization of AGT1, AGT1 was expressed with rBAT in HEK293 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The deletion or mutation of the C-terminal signal of b 0,+ AT (Slc7a9) does not prevent complex formation, but leads to the formation of an inactive complex. 45 Interestingly, mutations in the gene encoding the heavy chain or accessory protein rBAT (Slc3a1) as well as in its interacting light chain b 0,+ AT (Slc7a9) are associated with the autosomal disease cystinuria. Mutations on the gene encoding 4F2hc (Slc3a2), which associates with several members of the Slc7 family, are not connected to any physiological anomaly.…”
Section: Partner Proteinsmentioning
confidence: 99%
“…Also, there were 25 cases with the P482L homozygous mutation in SLC7A9 and six cases had heterozygous P482L mutations, as in this case. They suggested that the C-terminus of b 0,+ AT/BAT1, where P482L mutation is located, is important both for glycosylating the rBAT subunit and for promoting the trafficking of the cystine transporter from the endoplasmic reticulum to the Golgi apparatus 1 5. However, in the present case we do not yet know if the P482L missense mutation, which intensively suppresses functions of the cystine transporter rBAT–BAT1, alone caused the cystinuria, even in heterozygous form, or whether the second novel mutation in either SLC3A1 or SLC7A9 affected the clinical phenotype.…”
Section: Discussionmentioning
confidence: 99%